-2a+12+8a=5a-3a

Simple and best practice solution for -2a+12+8a=5a-3a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2a+12+8a=5a-3a equation:


Simplifying
-2a + 12 + 8a = 5a + -3a

Reorder the terms:
12 + -2a + 8a = 5a + -3a

Combine like terms: -2a + 8a = 6a
12 + 6a = 5a + -3a

Combine like terms: 5a + -3a = 2a
12 + 6a = 2a

Solving
12 + 6a = 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
12 + 6a + -2a = 2a + -2a

Combine like terms: 6a + -2a = 4a
12 + 4a = 2a + -2a

Combine like terms: 2a + -2a = 0
12 + 4a = 0

Add '-12' to each side of the equation.
12 + -12 + 4a = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 4a = 0 + -12
4a = 0 + -12

Combine like terms: 0 + -12 = -12
4a = -12

Divide each side by '4'.
a = -3

Simplifying
a = -3

See similar equations:

| 179/16-61/12 | | 3(2-s)=9 | | 31/3+x=53/4 | | 17+2n+3n-9=14n+15-9n-7 | | x+2x-63=0 | | 2(x-1)+1=9 | | 15x^2+2x-1=0factoring | | -2x-4(2x-8)=-18 | | 1.2(y+5)-(7.8+0.2y)=-5+3 | | 3(2x-2)+6=-12 | | 6=3-4x-5 | | 6z-10-z+5=0 | | 25/6-25/8 | | 3ab(2a^2+3b^3)= | | 8+32n=31+17 | | 0=4x+6-3x+2 | | 8x+36=5x+54 | | x-415.93=131.89 | | 29/12+4/3 | | -12/25=n/25 | | 1-4/a=5 | | x+10x+14=-7 | | 5x-6+10x=9 | | -6p-21q= | | 25/12+11/3 | | X^2-4/5x | | 7/10+2/5 | | v/4=72 | | 25=5x-2+4x | | 6(-4p+8)-5= | | 1/8+1/9 | | 18-7x=53 |

Equations solver categories